Anode for electrochemical device and electrochemical device
By incorporating a lithium carbonate layer and a solid electrolyte layer on the negative electrode of electrochemical devices, the internal resistance is reduced, addressing the issue of excessively thick SEI coatings and improving device performance.
Patent Information
- Application Number
- JP2022510672
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-26
- Filing Date
- 2021-03-25
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2041-03-25
AI Technical Summary
In electrochemical devices that utilize lithium ions, excessively thick solid electrolyte interface (SEI) coatings on the negative electrode material layer increase internal resistance, affecting the device's performance.
A negative electrode structure comprising a carbon material layer with a first layer of lithium carbonate and a second layer of solid electrolyte, where the second layer covers at least a part of the carbon material through the first layer, effectively controlling the thickness of both layers to minimize internal resistance.
The proposed solution effectively suppresses the increase in internal resistance, particularly at the negative electrode, thereby enhancing the performance and reliability of electrochemical devices.
Smart Images

Figure 0007656836000002 
Figure 0007656836000003 
Figure 0007656836000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode for an electrochemical device and an electrochemical device. [Background technology]
[0002] Electrochemical devices using a carbon material in which lithium ions are absorbed in a negative electrode material layer are known (see Patent Documents 1 to 3). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2014-123641 A [Patent Document 2] International Publication No. 2007 / 88604 Brochure [Patent Document 3] International Publication No. 2012 / 36249 Brochure Summary of the Invention [Problem to be solved by the invention]
[0004] In electrochemical devices that use lithium ions, a solid electrolyte interfacial film (i.e., SEI film) is formed on the negative electrode material layer during charging and discharging. The SEI film plays an important role in the charge and discharge reaction, but if the SEI film is formed too thick, the internal resistance of the electrochemical device increases. [Means for solving the problem]
[0005] One aspect of the present invention relates to a negative electrode for electrochemical devices, comprising a negative electrode core material and a negative electrode material layer supported on the negative electrode core material, the negative electrode material layer containing a carbon material, a surface layer portion of the negative electrode material layer having a first layer containing lithium carbonate and a second layer containing a solid electrolyte, at least a portion of the second layer covering at least a portion of the surface of the carbon material via the first layer. The thickness of the first layer is, for example, 1 nm or more and 50 nm or less.
[0006] Another aspect of the present invention relates to an electrochemical device comprising: a positive electrode including a positive electrode core material and a positive electrode material layer supported on the positive electrode core material; the negative electrode; a separator interposed between the positive electrode and the negative electrode; and an electrolyte.
[0007] Yet another aspect of the present invention relates to a method for producing a negative electrode for an electrochemical device, comprising the steps of: preparing a negative electrode comprising a negative electrode core material and a negative electrode material layer supported on the negative electrode core material, the negative electrode material layer containing a carbon material; and forming, on the negative electrode material layer, a first layer having a thickness of 1 nm or more and 50 nm or less, the first layer covering at least a part of a surface of the carbon material and containing lithium carbonate. Effect of the Invention
[0008] According to the present invention, an increase in the internal resistance (particularly the resistance of the negative electrode) of an electrochemical device can be effectively suppressed. The novel features of the present invention are set forth in the appended claims, but the present invention, both in terms of structure and content, together with other objects and features of the present invention, will be better understood from the following detailed description taken in conjunction with the drawings. [Brief description of the drawings]
[0009] [Figure 1] 1 is a vertical cross-sectional view showing a configuration of an electrochemical device according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a diagram showing a C1s spectrum in an XPS analysis of a lithium carbonate-containing region (first layer) having a thickness of 30 nm. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The negative electrode for electrochemical devices according to one embodiment of the present invention comprises a negative electrode core material and a negative electrode material layer supported on the negative electrode core material, the negative electrode material layer including a carbon material. The surface portion of the negative electrode material layer is constituted by a coating formed on the surface of the carbon material. The coating has a first layer and a second layer. At least a portion of the second layer covers at least a portion of the surface of the carbon material via the first layer. That is, at least a portion of the first layer is covered by the second layer. Such a first layer is interposed between the surface of the carbon material and the second layer, and serves as a base layer for the second layer.
[0011] Since at least the first layer contains lithium carbonate, the surface portion of the negative electrode material layer has a lithium carbonate-containing region. The lithium carbonate-containing region is a surface portion or a coating region in which the substantial presence of lithium carbonate is observed by analysis using, for example, X-ray photoelectron spectroscopy (XPS). The analysis method is not limited to XPS.
[0012] On the other hand, the second layer is an SEI coating and contains a solid electrolyte. The SEI coating is formed, for example, by a reaction between an electrolyte and a negative electrode in an electrochemical device. Since the electrolyte can pass through not only the second layer but also the first layer, the entire surface portion including the first and second layers may be referred to as the SEI coating. However, for the sake of convenience, the second layer is referred to as the SEI coating in this specification to distinguish it from the first layer.
[0013] The lithium carbonate-containing region is formed as a first layer constituting the surface layer of the negative electrode material layer before assembling the electrochemical device. When the lithium carbonate-containing region is formed in advance so as to cover at least a part of the surface of the carbon material, it is considered that in an electrochemical device assembled using the negative electrode, a homogeneous and moderately thick second layer (SEI coating) is formed on the surface of the carbon material by subsequent charging and discharging. Thus, an increase in the internal resistance of the electrochemical device is reduced. Here, the thickness of the first layer (lithium carbonate-containing region) may be, for example, 1 nm or more, and may be 5 nm or more when a longer-term effect is expected, and may be 10 nm or more when a more reliable effect is expected. However, if the thickness of the lithium carbonate-containing region exceeds 50 nm, the lithium carbonate-containing region itself becomes a resistance component, and the internal resistance of the electrochemical device increases. Therefore, the thickness of the lithium carbonate-containing region may be 50 nm or less, or may be 30 nm or less.
[0014] The thickness of the second layer may be, for example, 1 nm or more, may be 3 nm or more, and 5 nm or more is sufficient. If the thickness of the second layer exceeds 20 nm, the second layer itself becomes a resistance component, so that the internal resistance of the electrochemical device tends to increase in the early stage of the charge-discharge cycle. Therefore, the thickness of the second layer may be 20 nm or less, or may be 10 nm or less.
[0015] The ratio A / B of the thickness A of the first layer to the thickness B of the second layer is preferably 1 or less from the viewpoint of reducing the initial internal resistance. In this case, the thickness of the second layer is preferably 20 nm or less, and may be 10 nm or less. However, from the viewpoint of forming a second layer in good condition, it is desirable that A / B is 0.1 or more, and for example, the A / B ratio may be 0.2 or more.
[0016] The thicknesses of the first layer and the second layer are measured by analyzing the surface portion of the negative electrode material layer at multiple locations (at least five locations) of the negative electrode material layer. The average of the thicknesses of the first layer or the second layer obtained at the multiple locations may be regarded as the thickness of the first layer or the second layer. The negative electrode material layer used as the measurement sample may be peeled off from the negative electrode core material. In this case, the coating formed on the surface of the carbon material constituting the vicinity of the surface portion of the negative electrode material layer may be analyzed. Specifically, the carbon material covered with the coating may be collected from the region of the negative electrode material layer disposed on the side opposite to the side bonded to the negative electrode core material and used for analysis.
[0017] For example, the XPS analysis of the surface portion of the negative electrode material layer is performed by irradiating an argon beam onto the surface portion or the coating formed on the surface of the carbon material in the chamber of an X-ray photoelectron spectrometer, and observing and recording the change in each spectrum attributed to C1s or O1s electrons with respect to the irradiation time. In this case, the spectrum of the outermost surface of the surface portion may be ignored in order to avoid analytical errors. The thickness of the region where the peaks attributed to lithium carbonate are stably observed corresponds to the thickness of the lithium carbonate-containing region (here, the thickness of the first layer).
[0018] In the case of a completed negative electrode removed from an electrochemical device after a predetermined aging or at least one charge / discharge, the surface portion of the negative electrode material layer has an SEI coating (i.e., the second layer) containing a solid electrolyte produced in the electrochemical device. The thickness of the region where a peak attributable to the bond of the compound contained in the SEI coating is stably observed corresponds to the thickness of the SEI coating (i.e., the thickness of the second layer).
[0019] As the compound contained in the SEI coating, a compound containing an element that can be a label for the second layer is selected. As the element that can be a label for the second layer, for example, an element (e.g., F) that is contained in the electrolyte and is not substantially contained in the first layer may be selected. As the compound containing an element that can be a label for the second layer, LiF may be selected, for example.
[0020] When the second layer contains LiF, a substantial F1s peak attributable to LiF bonds is observed when the second layer is measured by X-ray photoelectron spectroscopy. In this case, the thickness of the region where the peak attributable to LiF bonds is stably observed corresponds to the thickness of the second layer.
[0021] On the other hand, the first layer does not usually contain LiF, and when the first layer is measured by X-ray photoelectron spectroscopy, a substantial F1s peak attributable to LiF bonds is not observed. Therefore, the thickness of the region where the peak attributable to LiF bonds is not stably observed may be taken as the thickness of the first layer.
[0022] An O1s peak attributed to lithium carbonate may also be observed in the SEI coating. However, the SEI coating formed in the electrochemical device has a different composition from the lithium carbonate-containing region formed in advance, so the two can be distinguished. For example, in an XPS analysis of the SEI coating, an F1s peak attributed to LiF bonds is observed, but a substantial F1s peak attributed to LiF bonds is not observed in the lithium carbonate-containing region. Furthermore, the amount of lithium carbonate contained in the SEI coating is small. As the Li1s peak, peaks derived from compounds such as ROCO2Li and ROLi may be detected.
[0023] When the lithium carbonate-containing region is analyzed by XPS, in addition to the first O1s peak attributable to the C=O bond, a second O1s peak attributable to the Li-O bond may be observed. The region of the coating present near the surface of the carbon material is considered to contain a small amount of LiOH or Li2O.
[0024] Specifically, when the first layer constituting the surface portion of the negative electrode material layer is analyzed in the depth direction, a first region in which a first peak (O1s attributed to a C=O bond) and a second peak (O1s attributed to a Li-O bond) are observed and the first peak intensity is greater than the second peak intensity, and a second region in which the first peak and the second peak are observed and the second peak intensity is greater than the first peak intensity may be observed in the order of increasing distance from the outermost surface of the surface portion. In addition, a third region may be further present that is closer to the outermost surface of the surface portion than the first region, and in which the first peak is observed but the second peak is not observed. The third region is easily observed when the thickness of the lithium carbonate-containing region is large.
[0025] The magnitude of the peak intensity may be determined based on the height of the peak from the baseline.
[0026] At the center in the thickness direction of the lithium carbonate-containing region, the C1s peak assigned to a C-C bond is usually not substantially observed, or even if it is observed, its intensity is half or less of the peak intensity assigned to a C=O bond.
[0027] Next, an electrochemical device according to one embodiment of the present invention includes a positive electrode having a positive electrode core material and a positive electrode material layer supported on the positive electrode core material, the negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. The negative electrode and the positive electrode constitute an electrode body together with the separator interposed therebetween. The electrode body is formed, for example, as a columnar wound body by winding a strip-shaped positive electrode and a negative electrode with a separator interposed therebetween. The electrode body may also be formed as a laminate by stacking a plate-shaped positive electrode and a negative electrode with a separator interposed therebetween.
[0028] The positive electrode material layer contains, for example, a conductive polymer as a positive electrode material. As the conductive polymer, for example, polyaniline or a derivative thereof can be used. Among electrochemical devices using lithium ions, electrochemical devices in which the positive electrode material layer contains a conductive polymer and the negative electrode material layer contains a carbon material are expected to be used in various fields such as vehicle applications. In such electrochemical devices, during charging, lithium ions in the electrolyte are absorbed into the negative electrode, and anions are adsorbed (doped) into the positive electrode. During discharging, lithium ions are released from the negative electrode into the electrolyte, and anions are desorbed (de-doped) from the positive electrode into the electrolyte. Since the conductive polymer is charged and discharged by doping and de-doping of anions, it has a small reaction resistance and is easy to achieve high output.
[0029] However, conductive polymers are organic, have low heat resistance, and can dissolve in solvents with strong electrolyte polarity. For example, the solvent in the electrolyte may decompose in a side reaction to produce alcohol. Conductive polymers such as polyaniline are easily affected by alcohol. Specifically, the non-aqueous electrolyte may decompose on the negative electrode, and the decomposition product may react with the moisture in the non-aqueous electrolyte to produce a small amount of alcohol. There is a possibility that polyaniline may dissolve due to alcohol. On the other hand, when the surface portion of the negative electrode material layer includes the first layer and the second layer, the structural stability of the surface portion is improved, so that side reactions are suppressed and the production of alcohol is suppressed. This is presumably because when the second layer, the SEI coating, is formed on the lithium carbonate-containing region, which is the first layer, as a base layer, the SEI coating is formed densely.
[0030] The anion includes, for example, a fluorine-containing anion. An electrolyte salt having such an anion has a high degree of dissociation and can provide an electrolyte solution with a low viscosity. In addition, by making the electrolyte contain a fluorine-containing anion, the withstand voltage characteristics of an electrochemical device can be improved.
[0031] Next, a method for producing a negative electrode for an electrochemical device according to one embodiment of the present invention includes a first step of preparing a negative electrode comprising a negative electrode core material and a negative electrode material layer supported on the negative electrode core material, the negative electrode material layer containing a carbon material, and a second step of forming a first layer having a thickness of 1 nm or more and 50 nm or less on the negative electrode material layer, the first layer covering at least a part of the surface of the carbon material and containing lithium carbonate.
[0032] The second step of forming the first layer on the negative electrode material layer so as to cover at least a part of the surface of the carbon material can be carried out by, for example, a gas phase method, a coating method, transfer method or the like.
[0033] Examples of the gas phase method include chemical vapor deposition, physical vapor deposition, and sputtering. For example, lithium carbonate may be deposited on the surface of the negative electrode material layer using a vacuum deposition device. The pressure in the device chamber during deposition is, for example, 10 -2 ~10 -5 Pa, the temperature of the lithium carbonate evaporation source may be 400 to 600°C, and the temperature of the negative electrode material layer may be -20 to 80°C.
[0034] As a coating method, a solution or dispersion containing lithium carbonate can be applied to the surface of the negative electrode using, for example, a microgravure coater, and then dried to form the first layer. The lithium carbonate content in the solution or dispersion is, for example, 0.3 to 2 mass %, and when a solution is used, the concentration may be equal to or lower than the solubility (for example, about 0.9 to 1.3 mass % in the case of an aqueous solution at room temperature).
[0035] Furthermore, a negative electrode can be obtained by carrying out a third step of forming a second layer containing a solid electrolyte so as to cover at least a part of the first layer. The surface portion of the obtained negative electrode material layer has a first layer and a second layer. The second layer is formed so that at least a part of it covers at least a part (preferably the entirety) of the surface of the carbon material via the first layer (i.e., the first layer serves as a base layer).
[0036] The third step is performed in a state where the negative electrode material layer is in contact with the electrolyte, and therefore may also serve as at least a part of a pre-doping step of lithium ions into the negative electrode material layer. For example, metallic lithium may be used as a source of lithium ions to be pre-doped.
[0037] The third step includes, for example, an aging step of forming an electrochemical device including a lithium ion source, and then applying a predetermined charging voltage (e.g., 3.4 to 4.0 V) between the terminals of the positive electrode and the negative electrode for a predetermined time (e.g., 1 to 75 hours) to complete pre-doping of lithium ions into the negative electrode. Alternatively, the third step includes a step of performing at least one charge and discharge cycle after forming the electrochemical device. As a result, an SEI coating (i.e., the second layer) including a solid electrolyte is formed on the negative electrode material layer.
[0038] The electrochemical device according to the present invention includes electrochemical devices such as lithium ion secondary batteries, lithium ion capacitors, and electric double layer capacitors, but is particularly suitable for configuring an intermediate electrochemical device between a lithium ion secondary battery and a lithium ion capacitor that uses a conductive polymer as the positive electrode material.
[0039] FIG. 1 is a schematic diagram showing the configuration of an electrochemical device 200 according to an embodiment of the present invention. The electrochemical device 200 includes an electrode assembly 100, a non-aqueous electrolyte (not shown), a metal cell case 210 with a bottom that accommodates the electrode assembly 100 and the non-aqueous electrolyte, and a sealing plate 220 that seals the opening of the cell case 210. A gasket 221 is disposed on the periphery of the sealing plate 220, and the inside of the cell case 210 is sealed by crimping the opening end of the cell case 210 to the gasket 221. A positive electrode current collector 13 having a through hole 13h in the center is welded to a positive electrode core material exposed portion 11x. One end of a tab lead 15 connected to the positive electrode current collector 13 is connected to the inner surface of the sealing plate 220 at the other end. Thus, the sealing plate 220 functions as an external positive electrode terminal. On the other hand, a negative electrode current collector 23 is welded to a negative electrode core material exposed portion 21x. The negative electrode current collector 23 is directly welded to a welding member provided on the inner bottom surface of the cell case 210. Therefore, the cell case 210 functions as an external negative electrode terminal.
[0040] Hereinafter, each component of the electrochemical device according to the embodiment of the present invention will be described in more detail, taking as an example an electrochemical device that uses a conductive polymer as the positive electrode material and a carbon material as the negative electrode material.
[0041] (Positive electrode core material) A sheet-shaped metal material is used for the positive electrode core material. The sheet-shaped metal material may be a metal foil, a metal porous body, an etched metal, or the like. The metal material may be aluminum, an aluminum alloy, nickel, titanium, or the like. The thickness of the positive electrode core material is, for example, 10 to 100 μm. A carbon layer may be formed on the positive electrode core material. The carbon layer is interposed between the positive electrode core material and the positive electrode material layer, and has a function of improving current collection from the positive electrode material layer to the positive electrode core material, for example.
[0042] (Carbon layer) The carbon layer is formed, for example, by depositing a conductive carbon material on the surface of the positive electrode core material, or by forming a coating of a carbon paste containing a conductive carbon material, and drying the coating. The carbon paste contains, for example, a conductive carbon material, a polymer material, and water or an organic solvent. The carbon layer may have a thickness of, for example, 1 to 20 μm. As the conductive carbon material, graphite, hard carbon, soft carbon, carbon black, etc. can be used. Among them, carbon black can form a thin carbon layer with excellent conductivity. As the polymer material, fluororesin, acrylic resin, polyvinyl chloride, styrene-butadiene rubber (SBR), etc. can be used.
[0043] (Positive electrode material layer) The positive electrode material layer contains a conductive polymer. The positive electrode material layer is formed, for example, by immersing a positive electrode core material having a carbon layer in a reaction solution containing a raw material monomer of the conductive polymer and electrolytically polymerizing the raw material monomer in the presence of the positive electrode core material. At this time, electrolytic polymerization is performed using the positive electrode core material as an anode, so that a positive electrode material layer containing a conductive polymer is formed so as to cover the carbon layer. The thickness of the positive electrode material layer can be controlled by the electrolytic current density, polymerization time, etc. The thickness of the positive electrode material layer is, for example, 10 to 300 μm per side.
[0044] The conductive polymer is preferably a π-conjugated polymer. For example, polypyrrole, polythiophene, polyfuran, polyaniline, polythiophene vinylene, polypyridine, or a derivative thereof may be used as the π-conjugated polymer. These may be used alone or in combination of two or more. The weight-average molecular weight of the conductive polymer is, for example, 1000 to 100000. The derivative of a π-conjugated polymer means a polymer having a basic skeleton of a π-conjugated polymer such as polypyrrole, polythiophene, polyfuran, polyaniline, polythiophene vinylene, or polypyridine. For example, polythiophene derivatives include poly(3,4-ethylenedioxythiophene) (PEDOT).
[0045] The positive electrode material layer may be formed by a method other than electrolytic polymerization. For example, a positive electrode material layer containing a conductive polymer may be formed by chemical polymerization of a raw material monomer. Also, a positive electrode material layer may be formed using a conductive polymer or a dispersion thereof that has been synthesized in advance.
[0046] The raw material monomer used in the electrolytic polymerization or chemical polymerization may be any polymerizable compound capable of producing a conductive polymer by polymerization. The raw material monomer may include an oligomer. Examples of the raw material monomer include aniline, pyrrole, thiophene, furan, thiophene vinylene, pyridine, or derivatives thereof. These may be used alone or in combination of two or more. Among them, aniline is easy to grow on the surface of the carbon layer by electrolytic polymerization.
[0047] Electrochemical polymerization or chemical polymerization can be performed using a reaction solution containing an anion (dopant). By doping a π-electron conjugated polymer with a dopant, excellent electrical conductivity can be achieved. For example, in chemical polymerization, the positive electrode core material is immersed in a reaction solution containing a dopant, an oxidizing agent, and a raw monomer, and then the positive electrode core material is pulled out of the reaction solution and dried. In electrochemical polymerization, the positive electrode core material and a counter electrode are immersed in a reaction solution containing a dopant and a raw monomer, and a current is passed between the positive electrode core material and the counter electrode, with the positive electrode core material serving as the anode.
[0048] Dopants include sulfate ions, nitrate ions, phosphate ions, borate ions, benzenesulfonate ions, naphthalenesulfonate ions, toluenesulfonate ions, and methanesulfonate ions (CF3SO3 - ), perchlorate ion (ClO4 - ), tetrafluoroborate ion (BF4 - ), hexafluorophosphate ion (PF6 - ), fluorosulfate ion (FSO3 - ), bis(fluorosulfonyl)imide ion (N(FSO2)2 - ), bis(trifluoromethanesulfonyl)imide ion (N(CF3SO2)2 -These may be used alone or in combination of two or more.
[0049] The dopant may be a polymer ion. Examples of the polymer ion include ions of polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacryl sulfonic acid, polymethacryl sulfonic acid, poly(2-acrylamido-2-methylpropane sulfonic acid), polyisoprene sulfonic acid, and polyacrylic acid. These may be homopolymers or copolymers of two or more monomers. These may be used alone or in combination of two or more.
[0050] (Positive current collector) The positive electrode current collector is a generally disk-shaped metal plate. It is preferable to form a through hole in the center of the positive electrode current collector, which serves as a passage for the non-aqueous electrolyte. The material of the positive electrode current collector is, for example, aluminum, aluminum alloy, titanium, stainless steel, etc. The material of the positive electrode current collector may be the same as the material of the positive electrode core material.
[0051] (Negative electrode core material) A sheet-shaped metal material is also used for the negative electrode core material. The sheet-shaped metal material may be a metal foil, a metal porous body, an etched metal, or the like. The metal material may be copper, a copper alloy, nickel, stainless steel, or the like. The thickness of the negative electrode core material is smaller than that of the positive electrode core material, for example, 10 to 100 μm.
[0052] (Negative electrode material layer) The negative electrode material layer includes a carbon material that electrochemically absorbs and releases lithium ions as a negative electrode active material. As the carbon material, graphite, non-graphitizable carbon (hard carbon), and easily graphitizable carbon (soft carbon) are preferable, and graphite and hard carbon are particularly preferable. The carbon material may be used in combination with other materials.
[0053] The negative electrode layer may contain, in addition to the negative electrode active material, a conductive agent, a binder, etc. Examples of the conductive agent include carbon black and carbon fiber, and examples of the binder include fluororesin, acrylic resin, rubber material, and cellulose derivatives.
[0054] The negative electrode material layer is formed, for example, by mixing a negative electrode active material, a conductive agent, a binder, etc. together with a dispersion medium to prepare a negative electrode mixture paste, applying the negative electrode mixture paste to a negative electrode current collector, and then drying the paste. The thickness of the negative electrode material layer is, for example, 10 to 300 μm per side.
[0055] The negative electrode material layer is pre-doped with lithium ions. This reduces the potential of the negative electrode, increasing the potential difference (i.e., voltage) between the positive electrode and the negative electrode, thereby improving the energy density of the electrochemical device. The pre-doping of lithium ions into the negative electrode material layer is carried out by impregnating metallic lithium together with the negative electrode into a non-aqueous electrolyte. The lithium ions are dissolved from the metallic lithium into the non-aqueous electrolyte and are absorbed into the negative electrode material layer. The amount of lithium pre-doped may be, for example, about 50% to 95% of the maximum amount that can be absorbed into the negative electrode material layer.
[0056] (Negative current collector) The negative electrode current collector is a generally disk-shaped metal plate. The material of the negative electrode current collector is, for example, copper, copper alloy, nickel, stainless steel, etc. The material of the negative electrode current collector may be the same as the material of the negative electrode core material.
[0057] (Separator) The separator may be a nonwoven fabric made of cellulose fibers, a nonwoven fabric made of glass fibers, a microporous membrane made of polyolefin, a woven fabric or a nonwoven fabric, etc. The thickness of the separator is, for example, 10 to 300 μm, and preferably 10 to 40 μm.
[0058] (electrolyte) The electrolyte has lithium ion conductivity and contains a lithium salt and a solvent for dissolving the lithium salt. The anions of the lithium salt are reversibly doped and dedoped into the positive electrode. The lithium ions derived from the lithium salt are reversibly absorbed and released into the negative electrode.
[0059] Examples of lithium salts include LiClO4, LiBF4, LiPF6, LiAlCl4, LiSbF6, LiSCN, LiCF3SO3, LiFSO3, LiCF3CO2, LiAsF6, LiB 10 Cl 10 , LiCl, LiBr, LiI, LiBCl4, LiN(FSO2)2, LiN(CF3SO2)2, etc. These may be used alone or in combination of two or more. Among them, salts having fluorine-containing anions are preferred. The concentration of the lithium salt in the non-aqueous electrolyte in the charged state (state of charge (SOC) 90 to 100%) is, for example, 0.2 to 5 mol / L.
[0060] Examples of the solvent that can be used include cyclic carbonates such as ethylene carbonate, propylene carbonate, and butylene carbonate, chain carbonates such as dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate, aliphatic carboxylates such as methyl formate, methyl acetate, methyl propionate, and ethyl propionate, lactones such as γ-butyrolactone and γ-valerolactone, chain ethers such as 1,2-dimethoxyethane (DME), 1,2-diethoxyethane (DEE), and ethoxymethoxyethane (EME), cyclic ethers such as tetrahydrofuran and 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, acetamide, dimethylformamide, dioxolane, acetonitrile, propionitrile, nitromethane, ethyl monoglyme, trimethoxymethane, sulfolane, methyl sulfolane, and 1,3-propane sultone. These may be used alone or in combination of two or more.
[0061] The electrolyte may contain various additives as necessary. For example, unsaturated carbonates such as vinylene carbonate, vinyl ethylene carbonate, and divinyl ethylene carbonate may be added as additives for forming a lithium ion conductive coating on the surface of the negative electrode.
[0062] [Example] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples.
[0063] Example 1 (1) Preparation of the positive electrode A carbon layer (thickness 2 μm) containing carbon black was formed on both sides of an aluminum foil (positive electrode core material) with a thickness of 25 μm. On the other hand, an aniline aqueous solution containing aniline and sulfuric acid was prepared. The positive electrode core material and the counter electrode were immersed in the aniline aqueous solution, and a current of 10 mA / cm was applied. 2 Electrochemical polymerization was performed for 20 minutes at a current density of 1000 sulphate ions (SO4 2- A film of a conductive polymer (polyaniline) doped with .) was grown on the carbon layer as a positive electrode material layer. At this time, a 10 mm wide exposed portion of the positive electrode core material was formed at the end along the longitudinal direction of the positive electrode core material. Next, the conductive polymer doped with sulfate ions was reduced to de-dope the doped sulfate ions, and then the positive electrode material layer was thoroughly washed and dried. The thickness of the positive electrode material layer was 50 μm per side.
[0064] (2) Preparation of the negative electrode A copper foil (negative electrode core material) having a thickness of 10 μm was prepared. On the other hand, a mixed powder of 97 parts by mass of hard carbon, 1 part by mass of carboxy cellulose, and 2 parts by mass of styrene butadiene rubber was mixed with water in a mass ratio of 40:60 to prepare a negative electrode mixture paste. The negative electrode mixture paste was applied to both sides of the negative electrode core material and dried to form a negative electrode material layer having a thickness of 50 μm. A negative electrode core material exposed portion having a width of 10 mm was formed at the end along the longitudinal direction of the negative electrode core material.
[0065] Then, a lithium carbonate source was introduced into the chamber of the device, and a first layer containing lithium carbonate was formed on the negative electrode material layer by a gas-phase method. The pressure in the chamber was 10 -2 The pressure was 10 Pa. The temperature of the negative electrode was -10°C. The temperature of the lithium carbonate evaporation source was 500°C. The thickness of the first layer was changed as shown in Table 1 to obtain negative electrodes A1 to A9 of the examples and negative electrode B1 of the comparative example. In addition, in the negative electrode B1 of the comparative example 1, the first layer containing lithium carbonate was not formed in the negative electrode material layer.
[0066] [Rating 1] The surface of the negative electrode layer was subjected to XPS analysis to measure the thickness of the lithium carbonate-containing region (first layer). For the XPS analysis, an X-ray photoelectron spectrometer (product name: Model 5600, manufactured by ULVAC-PHI, Inc.) was used. The measurement conditions are as follows:
[0067] X-ray source: Al-mono (1486.6eV) 14kV / 200W Measurement diameter: 800μmφ Photoelectron take-off angle: 45° Etching conditions: Acceleration voltage 3 kV, etching rate approximately 3.1 nm / min (SiO2 equivalent), raster area 3.1 mm x 3.4 mm
[0068] FIG. 2 is a graph showing a C1s spectrum obtained by XPS analysis of the first layer of the negative electrode material layer of negative electrode A4 in Example 4. In FIG.
[0069] According to Figure 2, peaks of C-C bonds, etc., which are presumed to be impurity carbon, are observed on the outermost surface of the first layer, but they rapidly decrease at a depth of about 1 to 3 nm in the first layer, and almost disappear at a depth of 10 to 20 nm. The peaks of C-C bonds, etc. observed in the deeper part are presumed to be peaks derived from hard carbon in the active material. On the other hand, peaks attributed to C=O bonds are constantly observed from the outermost surface of the first layer to a depth of 30 nm.
[0070] (3) Preparation of the electrode body The positive and negative electrodes were wound in a columnar shape with a cellulose nonwoven separator (thickness 35 μm) in between to form an electrode body. At this time, the positive electrode core exposed portion was protruding from one end face of the wound body, and the negative electrode core exposed portion was protruding from the other end face of the electrode body. A disk-shaped positive electrode current collector and a disk-shaped negative electrode current collector were welded to the positive electrode core exposed portion and the negative electrode core exposed portion, respectively.
[0071] (4) Preparation of non-aqueous electrolyte A solvent was prepared by adding 0.2 mass% vinylene carbonate to a mixture of propylene carbonate and dimethyl carbonate in a volume ratio of 1:1. LiPF6 was dissolved in the obtained solvent as a lithium salt at a predetermined concentration, and hexafluorophosphate ions (PF6 - A non-aqueous electrolyte having the following structure was prepared.
[0072] (5) Assembly of electrochemical devices The electrode body was housed in a bottomed cell case having an opening, and a tab lead connected to the positive electrode current collector was connected to the inner surface of the sealing plate, and further, a negative electrode current collector was welded to the inner bottom surface of the cell case. After putting a non-aqueous electrolyte together with a metallic lithium foil serving as a source of lithium ions to be pre-doped into the cell case, the opening of the cell case was sealed with a sealing plate, and an electrochemical device as shown in FIG. 1 was assembled. The amount of lithium to be pre-doped was set so that the negative electrode potential in the non-aqueous electrolyte after the completion of pre-doping was 0.2 V or less relative to metallic lithium. The electrochemical devices using the negative electrodes A1 to A9 of the embodiment are referred to as cells A1 to A9 of the embodiment 1 to 9. The electrochemical device using the negative electrode B1 of the comparative example 1 is referred to as cell B1 of the comparative example 1.
[0073] After that, the battery was aged for a predetermined time (10 to 80 hours) at 60°C while applying a charging voltage of 3.8V between the terminals of the positive electrode and the negative electrode, completing the pre-doping of lithium ions into the negative electrode. The thickness of the second layer varies depending on the aging temperature and time. Here, the second layer was controlled to be in the range of 5nm to 25nm.
[0074] [Rating 2] The surface portion of the negative electrode material layer of the negative electrode removed from the electrochemical device was analyzed by XPS in the same manner as above, and it was confirmed that an SEI coating (second layer) having the thickness shown in Table 1 was formed.
[0075] [Rating 3] <Initial characteristics> Immediately after aging, the electrochemical device was charged at a voltage of 3.8 V, and then the capacitance was measured. In addition, the electrochemical device was discharged from a voltage of 3.8 V for a predetermined time, and the internal resistance (initial DCR) was measured from the amount of voltage drop during the discharge.
[0076] <Characteristics after charge / discharge cycles> Charge and discharge were repeated 100,000 cycles in the range of 3.8 V to 2.2 V, and then the capacitance and internal resistance (DCR) were similarly determined.
[0077] <Anode reliability> The thickness of the negative electrode layer was measured before assembling the electrochemical device and after the above-mentioned charge-discharge cycle. The smaller the change in thickness of the negative electrode layer, the more reliable it is.
[0078] The results are shown in Table 1.
[0079] [Table 1]
[0080] Comparing Examples 1 to 9 with Comparative Example 1, it is found that forming the first layer makes it easier to control the thickness of the second layer, reduces the initial DCR, and provides an electrochemical device with excellent negative electrode reliability. It is also found that, provided that the thickness of the first layer is not extremely large, the smaller the thickness of the second layer, the lower the initial DCR can be.
[0081] The small change in thickness of the negative electrode means that the SEI film formed at the beginning is stable and is unlikely to be damaged or regenerated. Therefore, in each example, the capacity retention rate is high and the DCR increase rate is small.
[0082] It can be seen that even when the first layer is only 0.5 nm thick, the capacity retention rate is significantly higher and the DCR increase rate is significantly lower than in Comparative Example 1. The results in Table 1 show that a sufficiently significant effect can be obtained if the thickness of the first layer is 1 μm to 5 μm. [Industrial Applicability]
[0083] The electrochemical device according to the present invention is suitable for use in vehicles, for example. [Explanation of symbols]
[0084] 100: Electrode body 10: Positive electrode 11x: Positive electrode core exposed part 13: Positive current collector 15: Tabreed 20: Negative electrode 21x: Exposed part of negative electrode core material 23: Negative electrode current collector 30: Separator 200: Electrochemical devices 210: Cell case 220: Sealing board 221: Gasket
Claims
1. The negative electrode battery includes a negative electrode core material and a negative electrode material layer supported on the negative electrode core material, the negative electrode material layer contains a carbon material, the surface layer portion of the negative electrode material layer has a first layer containing lithium carbonate and a second layer containing a solid electrolyte, at least a portion of the second layer covers at least a portion of a surface of the carbon material via the first layer, A negative electrode for electrochemical devices, wherein a ratio of a thickness A of the first layer to a thickness B of the second layer: A / B is 0.1 or more and 1 or less.
2. the second layer contains lithium carbonate; 2. The negative electrode for electrochemical devices according to claim 1, wherein a content of said lithium carbonate contained in said second layer is less than a content of said lithium carbonate contained in said first layer.
3. 2. The negative electrode for an electrochemical device according to claim 1, wherein the first layer has a thickness of 1 nm or more and 50 nm or less.
4. 4. The negative electrode for electrochemical devices according to claim 1, wherein the second layer has a thickness of 5 nm or more and 15 nm or less.
5. When the first layer is measured by X-ray photoelectron spectroscopy, a substantial F1s peak attributable to a LiF bond is not observed; 5. The negative electrode for electrochemical devices according to claim 1, wherein a substantial F1s peak attributable to a LiF bond is observed when the second layer is measured by X-ray photoelectron spectroscopy.
6. a positive electrode including a positive electrode core material and a positive electrode material layer supported on the positive electrode core material; The negative electrode according to any one of claims 1 to 5, a separator interposed between the positive electrode and the negative electrode; and an electrolyte.
7. The electrochemical device of claim 6 , wherein the positive electrode material layer comprises a conductive polymer.
8. 8. The electrochemical device of claim 6 or 7, wherein the electrolyte comprises lithium ions and fluorine-containing anions.
9. preparing a negative electrode comprising a negative electrode core material and a negative electrode material layer supported on the negative electrode core material, the negative electrode material layer including a carbon material; forming a first layer having a thickness of 1 nm to 50 nm, the first layer covering at least a portion of a surface of the carbon material and containing lithium carbonate; forming a second layer including a solid electrolyte so as to cover at least a portion of the first layer; having a ratio of a thickness A of the first layer to a thickness B of the second layer: A / B is 0.1 or more and 1 or less.
Citation Information
Patent Citations
Lighium battery
JP1995201357A
Nonaqueous electrolyte battery and its manufacture
JP1995302617A
Nonaqueous electrolyte secondary battery
JP1999120992A
Negative electrode and battery
JP2005216601A
Electrochemical device
JP2014123641A